Frequent nightmares in Chinese patients undergoing methadone maintenance therapy: prevalence, correlates, and their association with functional impairment - Zhong, Bao-Liang (Neuropsychiatr Dis Treat, 2019)
PURPOSE: Nightmares are associated with many negative health outcomes; however, little is known about the characteristics of nightmares in heroin-dependent patients (HDPs). This study examined the prevalence and correlates of frequent nightmares (FNs) and their association with functional impairment in Chinese patients undergoing methadone maintenance therapy (MMT). PATIENTS AND METHODS: In total, 603 Chinese HDPs from three MMT clinics in Wuhan, China, completed this survey. FNs were defined as reporting nightmares at least once a week. The Sheehan Disability Scale (ShDS) was used to assess the severity of functional impairment of patients. A standardized questionnaire was used to collect data on socio-demographics, drug use characteristics, physical health, mental health, and insomnia. RESULTS: The prevalence of FNs in Chinese HDPs receiving MMT was 25.9%. Factors significantly associated with nightmares among MMT HDPs included an educational attainment of senior high school and above (OR=2.73, P<0.001), unemployment (OR=3.16, P<0.001), a history of re-education through forced labor (OR=3.14, P<0.001), injecting heroin before MMT (OR=3.62, P=0.002), a high dose of methadone (>70 mg/day) (OR=2.03, P=0.006), use of hypnotics (OR=1.91, P=0.044), the presence of hepatitis B virus core antibody (OR=4.63, P<0.001), pain (OR=3.20, P<0.001), anxiety (OR=2.06, P=0.039), and insomnia (OR=5.75, P<0.001). After controlling for potential confounders, nightmares were still significantly associated with a higher ShDS score (β=2.718, P=0.006). CONCLUSION: FNs are prevalent among Chinese HDPs receiving MMT and significantly associated with functional impairment. Nightmares are a clinically relevant phenomenon in Chinese MMT clinics, which deserves more clinical and research attention.